Clostridium butyricum Protects Against Pancreatic and Intestinal Injury After Severe Acute Pancreatitis via Downregulation of MMP9 - Yan, Qingqing; Jia, Lin; Wen, Biyan; Wu, Yao; Zeng, Yanbo; Wang, Qing (Frontiers in Pharmacology, 2022)
Background: Evidence have shown that gut microbiota plays an important role in the development of severe acute pancreatitis (SAP). In addition, matrix metalloproteinase-9 (MMP9) plays an important role in intestinal injury in SAP. Thus, we aimed to determine whether gut microbiota could regulate the intestinal injury during SAP via modulating MMP9. Methods: In this study, the fecal samples of patients with SAP (n = 72) and healthy controls (n = 32) were analyzed by 16S rRNA gene sequencing. In addition, to investigate the association between gut microbiota and MMP9 in intestinal injury during SAP, we established MMP9 stable knockdown Caco2 and HT29 cells in vitro and generated a MMP9 knockout (MMP9−/−) mouse model of SAP in vivo. Results: We found that the abundance of Clostridium butyricum (C. butyricum) was significantly decreased in the SAP group. In addition, overexpression of MMP9 notably downregulated the expressions of tight junction proteins and upregulated the expressions of p-p38 and p-ERK in Caco2 and HT29 cells (p < 0.05). However, C. butyricum or butyrate treatment remarkably upregulated the expressions of tight junction proteins and downregulated the expressions of MMP9, p-p38 and p-ERK in MMP9-overexpressed Caco2 and HT29 cells (p < 0.05). Importantly, C. butyricum or butyrate could not affect the expressions of tight junction proteins, and MMP9, p-p38 and p-ERK proteins in MMP9-knockdown cells compared with MMP9-knockdown group. Consistently, C. butyricum or butyrate could not attenuate pancreatic and intestinal injury during SAP in MMP9−/− mice compared with the SAP group. Conclusion: Collectively, C. butyricum could protect against pancreatic and intestinal injury after SAP via downregulation of MMP9 in vitro and in vivo.